Biển Đông - Trương Ngọc An; Nguyễn Tác An; Đặng Ngọc Thanh; Nguyễn Tiến Cảnh; Nguyễn Văn Chung (Nxb. Hà Nội, 2009)
Nghiên cứu khu hệ sinh vật vùng biển, nguồn lợi sinh vật vùng biển và sinh thái vùng biển Việt Nam